MANUSIA DAN POHON DALAM LUKISAN POST-IMPRESIONISME - ROMIYANSYAH, Drs. Abd. Hafiz, M.Pd, Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2017)
This final project aims to show a good result and a bad tree for humans with the natural surroundings, and shows the importance of the role of trees for humans and depict visually in the style of post-impressionism. Humans can not live well if it failed to establish harmony in the environment and interact with nature where he lives. That man is a microcosm and the macrocosm of the universe is. How important the mutually supportive relationship between activity and human consciousness with the natural environment. Although the World Earth Day is always celebrated annually on 22 April, but the awareness of the community to maintain and protect the earth and the prosecution of perpetrators of illegal logging is still low.Keywords: People, Trees, Painting Post-Impressionism.